2021
DOI: 10.1016/j.artd.2021.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Time for an Update? A Look at Current Guidelines for Venous Thromboembolism Prophylaxis After Hip and Knee Arthroplasty and Hip Fracture

Abstract: Venous thromboembolism is a well-established complication of total hip and knee arthroplasty and hip fracture surgery. Clinical practice guidelines have been proposed to help clinicians provide prophylaxis against this risk. However, most guidelines reference data that are becoming outdated because of new advances in perioperative protocols. Recent data would suggest that aspirin may be appropriate for most patients after total hip and knee replacement and a more potent chemoprophylaxis for higher risk patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 33 publications
0
15
0
1
Order By: Relevance
“…Unidos, e baixas taxas de complicação, o tromboembolismo venoso com incidência aproximada de 0,6 a 1,5% representa aumento das complicações, taxa de internação e morbimortalidade nestes pacientes (Santana et al, 2020). Apesar de ser uma complicação conhecida, a incidência de tromboembolismo venoso após cirurgias ortopédicas maiores (artroplastias de quadril e joelho e fratura do quadril) diminui com a profilaxia mecânica e farmacológica, avanço das técnicas cirúrgicas e anestésicas, melhor controle da dor pós-operatória e mobilidade precoce (Muscatelli et al, 2021).…”
Section: Resultsunclassified
“…Unidos, e baixas taxas de complicação, o tromboembolismo venoso com incidência aproximada de 0,6 a 1,5% representa aumento das complicações, taxa de internação e morbimortalidade nestes pacientes (Santana et al, 2020). Apesar de ser uma complicação conhecida, a incidência de tromboembolismo venoso após cirurgias ortopédicas maiores (artroplastias de quadril e joelho e fratura do quadril) diminui com a profilaxia mecânica e farmacológica, avanço das técnicas cirúrgicas e anestésicas, melhor controle da dor pós-operatória e mobilidade precoce (Muscatelli et al, 2021).…”
Section: Resultsunclassified
“…The ideal thromboprophylactic regimen must be costeffective and easy to administer, with the ultimate goal being the prevention of fatal PE, whilst minimising anticoagulantrelated complications, such as bleeding and wound problems [32]. There were no fatal PE in the UHRAP group, with only four cases of non-fatal PE (0.96%), which, despite the ultra-high-risk nature of the patients, confirmed that the use of prophylactic filters reduced the risks to a level similar to, or indeed below, that for standard TJA patients.…”
Section: Discussionmentioning
confidence: 99%
“…All patients undergoing THA and TKA are at high risk of VTE, but the ultra-high-risk arthroplasty patients (UHRAP) group includes those with a history of DVT (particularly proximal, chronic or unprovoked), PE, a genetic clotting disorder causing a hypercoagulable state, or in whom anticoagulation is contra-indicated due to medical reasons, such as previous bleeding complications or failure, resulting in breakthrough VTE. Other risk factors include increasing age, a higher comorbidity burden especially chronic obstructive pulmonary disease (COPD), congestive cardiac failure (CCF) and cerebrovascular accident (CVA), overall poor health status as classified by American Society of Anaesthesiologists (ASA 3 and above, [31]) and those undergoing prolonged complex surgery [14,15,32].…”
Section: Introductionmentioning
confidence: 99%
“…Although some cases of epidural hematoma after locoregional anesthesia have been described in patients receiving acetylsalicylic acid or nonsteroidal anti-inflammatory drugs, the incidence of this complication does not appear to be significantly increased in patients treated with antiplatelet drugs [22,23]. According to the existing knowledge, locoregional anesthesia is considered suitable for patients on antiplatelet therapy [15,24]. Similar conclusions may not be drawn for ticlopidine because there is not yet sufficient evidence in the literature.…”
Section: Management Of Antiplatelets/anticoagulant Drugsmentioning
confidence: 99%